Integrating a learning management system with a student assignments digital repository : a case study - Díaz, Francisco Javier
The integration of different platforms and information Systems in the academic environment is highly important and quite a challenge within the field of Information Technology. This integration allows for higher resource availability and improved interaction among intervening actors. In the field of e-Learning, where Learning Management Systems are used to develop the courses, their integration with other platforms and applications is more than interesting, in particular with Digital Repositories. This article describes the integration of the Moodle LMS, used by the School for the last seven years, with the DSpace repository, currently widely spread as well. The integration process consists of two stages, in order to establish full communication to and from the repository. For communication from Moodle to the repository, with the goal of consulting and transferring elements from DSpace, modules already implemented for both platforms were used. The current stage is implementing a specific module in order to establish communication in the other direction and allow transferring resources and learning objects from the LMS to the repository. This module is very useful for educational material that can be made publicly available through a repository and thus transcending the borders of an educational environment. The initial implementation is oriented towards the publication of work done by the students and presented for evaluation through the Moodle platform. The incorporation of metadata to the published resource is automatic, taking context information from the platform, and at a later stage, with the intervention of librarians, who contribute their knowledge in the classification.